DISTALLY BASED SUPERFICIAL SURAL ARTERY FLAP - Ashish Gupta; P J Prakash; Binu P Thomas; Prema Dhanraj (Indian Journal of Plastic Surgery)
We describe our experience with the use of distally based superficial sural artery flap for coverage of defects in lower third of leg and foot in 12 patients. In 9 patients the flap was successfully transferred and in 3 cases marginal necrosis of flap occurred. This flap has a constant and reliable blood supply and does not sacrifice a major artery. Other advantages of this flap are easy dissection and is a one stage procedure. In most patients the skin graft site is cosmetically unacceptable.